2020
DOI: 10.1007/s40268-020-00294-4
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Clodronate in Long-Term Treatment of Symptomatic Knee Osteoarthritis: A Randomized Controlled Study

Abstract: Background and Objective Clodronate is a nitrogen-free bisphosphonate that is widely and effectively used in the treatment of many osteo-metabolic disorders. The objective of our study was to evaluate the effectiveness of clodronate in reducing pain and bone marrow edema in knee osteoarthritis. Methods In total, 74 patients were included in the study. Group 1 received intramuscular clodronate 200 mg daily for 15 days and then once weekly for the next 11.5 months; group 2 received intramuscular clodronate 200 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Our results may partially elucidate why results differ between trials, observational studies, and meta-analyses (5,(11)(12)(13)(14)(15)(16)33) examining the benefit of bisphosphonates for various radiographic and symptomatic outcomes. Prior to examining effects, it is Weighted by stabilized and truncated (at the 5th and 95th percentile) inverse probability censor weights.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Our results may partially elucidate why results differ between trials, observational studies, and meta-analyses (5,(11)(12)(13)(14)(15)(16)33) examining the benefit of bisphosphonates for various radiographic and symptomatic outcomes. Prior to examining effects, it is Weighted by stabilized and truncated (at the 5th and 95th percentile) inverse probability censor weights.…”
Section: Discussionmentioning
confidence: 86%
“…Our results may partially elucidate why results differ between trials, observational studies, and meta‐analyses ( 5,11–16,33 ) examining the benefit of bisphosphonates for various radiographic and symptomatic outcomes. Prior to examining effects, it is necessary to understand the interplay of OA risk factors, the potential mechanism of benefit that bisphosphonates may have, and in which populations these protective effects would demonstrate the most benefit.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This phenotypedependency has been demonstrated in pre-clinical research, where bisphosphonates are differentially effective in reducing pain and not only bone but also cartilage pathology in OA models with high versus low bone turnover. [106][107][108][109] Recently, clodronate (n=74) 110 and neridronate (n=64) 111 have been successfully used for the treatment of knee and hand OA, with an interesting efficacy on BMLs, although the sample sizes are small. An individual patient data meta-analysis for examining their efficacy in specific knee OA subtypes is still ongoing.…”
Section: Antiresorptive Drugs: Bisphosphonates and Denosumabmentioning
confidence: 99%
“…Although Clo is commonly used as anti-osteoporotic drug, recently many evidences have shown that Clo has also been successfully tested in erosive osteoarthritis (OA) upon intra-articular and parenteral administration 8 , 10 , 11 . In this setting, Clo has been demonstrated to regulate the biosynthesis and the release of NO, expression of cycloxygenase 2 (COX 2 ) and pro-inflammatory cytokines such as TNF-α, IL-1β that are known to promote cartilage erosion, subchondral bone alterations and to inhibit progenitors maturation into chondrocytes in OA early stages 7 , 12 15 .…”
Section: Introductionmentioning
confidence: 99%